Experimental insights into the effects of Mg addition and ECAP processing on the anomalous anneal strengthening of pure zinc - Zahra Ramezanroudi; Sara Sarvarpour; Reza Alizadeh (Journal of Materials Research and Technology)
Use of zinc in various applications is constrained by its weak mechanical properties. In this study, the effects of different strategies, including alloying (by means of 1 wt% Mg addition), heat treatment (by means of annealing at different temperatures and times) and severe plastic deformation (by means of performing equal channel angular pressing, ECAP) on the mechanical properties of zinc were evaluated. It was found that the addition of 1 wt% Mg significantly enhances the compressive yield strength of pure zinc by 52 %, increasing it from 138 MPa to 210 MPa, primarily due to grain refinement and the formation of secondary Mg2Zn11 and MgZn2 phases. Both pure zinc and Zn–1Mg alloy exhibit strengthening, instead of softening, during prolonged annealing at 300 °C; notably, the Zn–1Mg alloy demonstrates considerable strengthening attributed to morphological changes in secondary phases, grain boundary evolution, dislocation rearrangement, and phase interface interactions. Although ECAP processing refines and homogenizes the Zn–1Mg microstructure, it does not markedly improve mechanical strength. Nevertheless, annealing of the ECAP-processed alloy results in the highest compressive strength recorded in this study, highlighting the synergistic effect of combined processing and heat treatment on mechanical performance.